Centrosomal Localisation of the Cancer/Testis (CT) Antigens NY-ESO-1 and MAGE-C1 Is Regulated by Proteasome Activity in Tumour Cells - Pagotto, Anna (Public Library of Science, 2013)
The Cancer/Testis (CT) antigen family of genes are transcriptionally repressed in most human tissues but are atypically re-expressed in many malignant tumour types. Their restricted expression profile makes CT antigens ideal targets for cancer immunotherapy. As little is known about whether CT antigens may be regulated by post-translational processing, we investigated the mechanisms governing degradation of NY-ESO-1 and MAGE-C1 in selected cancer cell lines. Inhibitors of proteasome-mediated degradation induced the partitioning of NY-ESO-1 and MAGE-C1 into a detergent insoluble fraction. Moreover, this treatment also resulted in increased localisation of NY-ESO-1 and MAGE-C1 at the centrosome. Despite their interaction, relocation of either NY-ESO-1 or MAGE-C1 to the centrosome could occur independently of each other. Using a series of truncated fragments, the regions corresponding to NY-ESO-1(91-150) and MAGE-C1(900-1116) were established as important for controlling both stability and localisation of these CT antigens. Our findings demonstrate that the steady state levels of NY-ESO-1 and MAGE-C1 are regulated by proteasomal degradation and that both behave as aggregation-prone proteins upon accumulation. With proteasome inhibitors being increasingly used as front-line treatment in cancer, these data raise issues about CT antigen processing for antigenic presentation and therefore immunogenicity in cancer patients.